Sharia Maqashid Index and Its Effect on The Value of The Firm of Islamic Commercial Bank in Indonesia - Wahyuni, Sri; Pujiharto, Pujiharto; Hartikasari, Annisa Ilma (Universitas Muhammadiyah Surakarta, 2020)
This research aimed to measure the performance of Islamic banks using the Sharia Maqashid Index approach and examine its effect on firm value. This current research used the Islamic Commercial Banks in Indonesia as its object, with an observation period of 2012-2018. The sampling method used was purposive sampling. It was done by setting certain criteria according to the purpose of the research and produced a total of 9 Islamic Commercial Banks (ICB) as the research sample. Sharia Maqashid Index measurement results showed the ICB performance ranked from the highest to the lowest were as follows: 1) Mandiri Syariah; 2) Panin Syariah; 3) BCA Syariah 4) Bank Muammalat Indonesia; 5) BRI Syariah; 6) Bukopin Syariah; 7) BNI Syariah; 8) Mega Syariah; 9) Maybank Syariah. The results of hypothesis testing indicated that the sharia maqashid index has an impact on increasing the value of Islamic Commercial Banks. The results of this research provided a significant contribution to the management of Islamic banks, Bank Indonesia, and the Islamic Financial Accounting Standards Development Board. For managers of Islamic banks, the results of this research can be used as performance evaluations so that the goals of establishing Islamic banks, one of which is the public interest, can be achieved. For Bank Indonesia, the results of this research can be used to design policies that can encourage Islamic banks to improve sharia-based performance. As for the Islamic Accounting Standards Board, it can be used to develop sharia compliance audit standards that can guarantee the application of sharia principles in Islamic bank operations.